Proposition of Regression Equations to Determine Outdoor Thermal Comfort in Tropical and Humid Environment - Sangkertadi Sangkertadi; Reny Syafriny (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2012)
This study is about field experimentation in order to construct regression equations of perception of thermalcomfort for outdoor activities under hot and humid environment. Relationships between thermal-comfort perceptions, micro climate variables (temperatures and humidity) and body parameters (activity, clothing, body measure) have been observed and analyzed. 180 adults, men, and women participated as samples/respondents. This study is limited for situation where wind velocity is about 1 m/s, which touch the body of the respondents/samples. From questionnaires and field measurements, three regression equations have been developed, each for activity of normal walking, brisk walking, and sitting.